Search for anomalous triple gauge couplings in WW and WZ production in lepton plus jet events in proton-proton collisions at root s=13 TeV - Sirunyan, A. M. (2019)
A search is presented for three additional operators that would lead to anomalous WW gamma or WWZ couplings with respect to those in the standard model. They are constrained by studying events with two vector bosons; a W boson decaying to e nu or mu nu, and a W or Z boson decaying hadronically, reconstructed as a single, massive, large-radius jet. The search uses a data set of proton-proton collisions at a centre-of-mass energy of 13 TeV, recorded by the CMS experiment at the CERN LHC in 2016, and corresponding to an integrated luminosity of 35.9 fb(-1). Using the reconstructed diboson invariant mass, 95% confidence intervals are obtained for the anomalous coupling parameters of -1.58 < c(WWW)/Lambda(2) < 1.59 TeV-2, -2.00 < c(W)/Lambda(2) < 2.65 TeV-2, and -8.78 < c(B)/Lambda(2) < 8.54 TeV-2, in agreement with standard model expectations of zero for each parameter. These are the strictest bounds on these parameters to date.